Dose calculation for spot scanning proton therapy with the application of a range shifter. (6th June 2017) - Zhang, Yang; Kerr, Matthew D; Guan, Fada; Hartman, Joris; Jiang, Bo; Sahoo, Narayan; Zhu, X Ronald; Gillin, Michael T; Qian, Wei; Zhang, Xiaodong
Abstract: Purpose. To build a correction factor dataset to improve accuracy of dose calculations for spot-scanning proton therapy with a range shifter employed. Material and method. Our synchrotron-based spot scanning proton therapy system has an energy range of 72.5–221.8 MeV. The Bragg peak chamber was used to perform the integral depth dose measurements in a water phantom with different air-gap sizes between the range shifter and the water phantom. Three typical energies of 151.0, 181.1 and 219.3 MeV and three air-gap sizes of 10, 20 and 30 cm were selected to perform the measurements. The measured data were used as the standard metrics for evaluating the accuracy of Monte Carlo simulations. The Monte Carlo platform TOPAS was used to simulate the transport of protons in the nozzle with a range shifter and the water phantom. The Monte Carlo generated dose data were used to build the dataset of dose correction factors for air gap effect. A treatment field from a multi-field treatment plan of a brain cancer case was selected to demonstrate the clinical significance of applying the dose correction factors. Result. The beam parameters in Monte Carlo simulations were finely tuned to make the simulated dose distributions match the measurements with the mean difference in the magnitude of 1.0%. The Monte Carlo generated correction factors for different beam energies and different depths in the water phantom show that for each specific beam energy the dose correction factor increases with the increase of air gap and decreases with the increase of depth in water, and larger correction factors are needed for higher beam energies. The gamma pass rate for the selected brain treatment field was improved from 80.4% to 97.8% after applying the dose correction factors. Conclusion. Applying the dose correction factor dataset for different air gaps between the range shifter and the target is a practical, low-cost solution to improve the accuracy of dose calculations for SSPT treatment plans.